2019
DOI: 10.1016/j.jmmm.2019.01.049
|View full text |Cite
|
Sign up to set email alerts
|

Phase diagrams of a 2D Ising spin-pseudospin model

Abstract: We consider the competition of magnetic and charge ordering in high-Tc cuprates within the framework of the simplified static 2D spin-pseudospin model. This model is equivalent to the 2D dilute antiferromagnetic (AFM) Ising model with charged impurities. We present the mean-field results for the system under study and make a brief comparison with classical Monte Carlo (MC) calculations. Numerical simulations show that the cases of strong exchange and strong charge correlation differ qualitatively. For a strong… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 50 publications
1
7
0
2
Order By: Relevance
“…We found that this critical temperature is determined by the maximum rate of change of the impurityspin pairs concentration and is proportional to the modulus of a difference between the exchange constant and the impurities interaction parameter. Unlike the dilute Ising chain, in the two-dimensional dilute Ising system with mobile impurities and in related models [52][53][54][55][56][57] , the previously considered orderings are the phase transitions at finite temperatures. If V < |J| and the impurities concentration n < n c , the spin ordering with the temperature lowering precedes to the phase separation when the domains containing only impurities or only spin centers occur.…”
Section: Discussionmentioning
confidence: 99%
“…We found that this critical temperature is determined by the maximum rate of change of the impurityspin pairs concentration and is proportional to the modulus of a difference between the exchange constant and the impurities interaction parameter. Unlike the dilute Ising chain, in the two-dimensional dilute Ising system with mobile impurities and in related models [52][53][54][55][56][57] , the previously considered orderings are the phase transitions at finite temperatures. If V < |J| and the impurities concentration n < n c , the spin ordering with the temperature lowering precedes to the phase separation when the domains containing only impurities or only spin centers occur.…”
Section: Discussionmentioning
confidence: 99%
“…Changes in the maximum MCE temperature related to changes in the chemical composition have been well demonstrated in [10,11,12]. However, the phase state of the system described by Hamiltonian (1) also depends on the ratio between the constants of exchange and density-density interactions, as was shown for a similar spin-pseudo-spin model [13,14,15,16]. In this work, we compare the MCE parameters in cases of strong and weak coupling; we also explore the possibility of detecting frustration in ground state of the system with weak coupling using magnetic entropy data.…”
Section: Introductionmentioning
confidence: 73%
“…At ∆ > 0 the results can be compared with the Blume-Capel model [28,29] or with the Blume-Emery-Griffiths model [30]. This limit of the spin-pseudospin model in the two-sublattice, nearest neighbor approximation and Ising form for the exchange interaction, was considered in sufficient detail in a series of papers [31,32,33,34,35,36] within MFA, Bethe cluster approach, and classical Monte-Carlo technique.…”
Section: Atomic Limitmentioning
confidence: 99%